The Effect of Interactive Multimedia-Based Learning on Students' Mathematical Problem Solving Ability - Angraini, Lilis Marina; Yosi Cahyaningtyas Fitri (EDUPEDIA Publisher, 2023)
This research was motivated by the low mathematical problem solving ability of students, and the online learning system during the covid-19 pandemic. This research aims to improve students’ mathematical problem solving ability through interactive multimedia-based teaching material as a support for online learning. This research type is a quantitative research (quasi-experimental) which was carried out at Universitas Islam Riau (UIR) and Universitas Pasir Pangaraian (UPP). The research subjects were students of mathematics education who took Structure Algebra course at UIR (experimental class) students of mathematics education and UPP (control class) in the 2021/2022 academic year. The data collection technique used is a mathematical problem solving ability test and the test result data is processed by statistical test. Normality test using Kolmogorov-Smirnov and homogeneity test using Levene and also t test. Based on the result of the t-test, a significance value of 0,025 < 0,05 was obtained. This means that there is an increase in the mathematical problem solving ability of student who receive from using interactive multimedia-based teaching material.